Relationship of parenting patterns in children aged 2-5 years with attitudes preventing stunting: A cross-sectional study - Amalia, Fitri; Siahaan, Joni (Indonesian Journal of Health Services, 2025)
Background: Childhood stunting remains a major global public health problem that affects growth, development, and long-term health outcomes among children under five years of age. Parenting behavior and preventive health attitudes within families play an important role in supporting child nutrition and growth during early childhood. Objective: This study aimed to analyze the relationship between parenting patterns in children aged 2–5 years and parental attitudes toward stunting prevention. Methods: This study employed a quantitative cross-sectional design involving 65 parents who had children aged 2–5 years in the Tarumajaya Public Health Center area. Participants were selected using a purposive sampling technique based on predefined inclusion criteria. Data were collected using a structured questionnaire that assessed parenting patterns and attitudes toward stunting prevention. Data analysis was performed using descriptive statistics and Fisher’s Exact Test to determine the association between variables. Results: The results showed that most parents applied democratic parenting patterns (90.8%), followed by authoritarian (4.6%), neglectful (3.1%), and permissive parenting (1.5%). The majority of respondents demonstrated positive attitudes toward stunting prevention (96.9%). The Fisher Exact statistical test indicated that parenting patterns were not significantly associated with attitudes toward stunting prevention (p = 0.092). Conclusion: Most parents demonstrate positive attitudes toward stunting prevention regardless of parenting patterns. Strengthening parental education and community-based health promotion may enhance preventive practices related to child growth and nutrition.